Business conditions and default risks across countries - Michael P. Pflüger; Stephan Russek (Institute for the Study of Labor (IZA), 2011)
The risk of default that business firms face is very significant and differs widely across countries. This paper explores the links between countries' business conditions and international trade embedment and the default risk at the country level from a theoretical point of view. Our main contribution is to set up a general equilibrium model which allows us to derive sharp predictions concerning how key factors which shape a country's business and trade environment impact on the default risk of firms which operate in these environments. The predictions are in accord with readily available data.
urn:nbn:de:101:1-201104133551
Keywords: F12; F13; F15; L25; 330; firm death; firm heterogeneity; business conditions and firm productivity; trade integration; Konkurs; Risiko; Standortfaktor; Außenwirtschaft; Unternehmen; Produktivität; Allgemeines Gleichgewicht; Theorie